Competitiveness as a Factor in the Sustainable Development of a Light Industry Enterprise - Nizomiddinov Jahonmirzo Zukhriddin oglu (International Journal on Human-Computing Studies, 2022)
The ongoing complex processes of reforming economic relations and the development of new market conditions for managing require new approaches to the organization of production and economic activities, principles and methods of enterprise management. In the course of economic reforms, enterprises have undergone significant changes, both in terms of the socio-economic nature of ownership, and in terms of the qualitative and quantitative characteristics of their production capabilities. The radically changed external environment required the skills of doing business in a competitive environment.